Name-writing proficiency, not length of name, is associated with preschool children’s emergent literacy skills - Puranik, Cynthia S. (2011)
The goals of this study were twofold: first, to examine whether preschool children’s name-writing proficiency differentiated them on other emergent reading and writing tasks, and second, to examine the effect of name length on preschool children’s emergent literacy skills including alphabet knowledge and spelling. In study 1, a range of emergent literacy tasks was administered to 296 preschool children aged 4–5 years. The more advanced name writers outperformed the less advanced name writers on all emergent literacy measures. Furthermore, children with longer names did not show superior performance compared to children with shorter names. In study 2, four measures of alphabet knowledge and spelling were administered to 104 preschool children. Once again, the more advanced name writers outperformed the less advanced name writers on the alphabet knowledge and spelling measures. Results indicated that having longer names did not translate into an advantage on the alphabet knowledge and spelling tasks. Name writing proficiency, not length of name appears to be associated with preschool children’s developing emergent literacy skills. Name writing reflects knowledge of some letters rather than a broader knowledge of letters that may be needed to support early spelling.